Evaluation of peptide secondary structure and intracellular uptake by introducing disubstituted amino acids into the amphipathic helical peptide C18AA - Takuma Kato; Go Ofuka; Ryota Kobayashi; Akiko Asano; Mitsunobu Doi (Results in Chemistry)
Amphipathic helical peptides are common among antimicrobial and cell membrane-permeable peptides, and amino acid substitutions within existing peptides have been an effective means of new peptide drug development. In the present study, we evaluated the effect of introducing a disubstituted amino acid (dAA), which has a stabilizing effect on the helical structure of the amphiphilic peptide C18AA, on the secondary structure of C18AA and its intracellular uptake. Computational analysis was also used to calculate the changes in the thermal stability of the secondary structure caused by substitution to dAAs. The results revealed that peptides that assumed a stable helical structure in aqueous solution showed higher intracellular uptake. It was also revealed that the type and position of the substituted amino acids significantly affected the peptide's secondary structure and intracellular uptake. These results indicate that use of dAAs may be a promising approach to improving the intracellular uptake of existing amphipathic helical peptides.